2017
DOI: 10.1155/2017/5197592
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 and socs3 Are Predictive Biomarkers of Dengue Hemorrhagic Fever

Abstract: Background Cytokines play important roles in the physiopathology of dengue infection; therefore, the suppressors of cytokine signaling (socs) that control the type and timing of cytokine functions could be involved in the origin of immune alterations in dengue. Objective To explore the association of cytokine and socs levels with disease severity in dengue patients. Methods Blood samples of 48 patients with confirmed dengue infection were analyzed. Amounts of interleukins IL-2, IL-4, IL-6, and IL-10, interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 54 publications
(89 reference statements)
3
37
0
Order By: Relevance
“…Studies have shown high levels of IL-6 in dengue infected liver sections and elevated IL-10 levels in patients with severe dengue (Oliveira et al, 2017;Pandey et al, 2015). Consistent with other findings (Oliveira et al, 2017;Pandey et al, 2015;Flores-Mendoza et al, 2017), we observed high levels of IFN-g, IL-6 and IL-10 late in the course of DENV2 infection. Although IL-10 was generally regarded as an anti-inflammatory cytokine, several studies suggested that IL-10 contributed to antitumor immunity by assisting the expansion of tumor-resident CD8 + T cells (Emmerich et al, 2012;Mumm et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown high levels of IL-6 in dengue infected liver sections and elevated IL-10 levels in patients with severe dengue (Oliveira et al, 2017;Pandey et al, 2015). Consistent with other findings (Oliveira et al, 2017;Pandey et al, 2015;Flores-Mendoza et al, 2017), we observed high levels of IFN-g, IL-6 and IL-10 late in the course of DENV2 infection. Although IL-10 was generally regarded as an anti-inflammatory cytokine, several studies suggested that IL-10 contributed to antitumor immunity by assisting the expansion of tumor-resident CD8 + T cells (Emmerich et al, 2012;Mumm et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…For example, dengue virus infection was reported to drive IL-10-mediated SOCS3 expression and the consequent inactivation of JAK/STAT pathways [37]. Additionally, a close association between cytokine imbalance and SOCS1/3 observed in patients with a severe dengue infection suggested that the combined analysis of SOCS1/3, IL-10, and IL-6 expression levels could identify at-risk patients for severe dengue [38]. In an intracerebral infection mouse model, SOCS proteins were upregulated in brain resident cells in response to infection with yellow fever virus [39].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of cytokines causing immune dysregulation is another mechanism that contributes to the increased susceptibility to secondary infections. For example, plasma levels of interleukin-10, which is a known immunosuppressant, are increased in dengue infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%